Overall survival of metastatic colorectal cancer in Lima: relationship with the KRAS gene mutational status - Aldecoa, Franklin (2020)
Objectives: the main goal for this study was to evaluate overall survival in mCRC patients with mutated vs. wild type KRAS gene (exon 2) status. Materials and methods: between January 2010 and December 2013, data from clinical records of mCRC patients from different hospitals in Lima, stating an assessment of the KRAS gene mutation status (exon 2), were analyzed. Kaplan-Meier survival estimates and Log-Rank or Breslow Test were used to compare the survival curves. Results: three-hundred and twenty cases were analyzed. There were 227 patients (70.93%) with wild type KRAS and 93 (29.07%) with mutated KRAS. The overall survival of mCRC patients and mutated KRAS was higher than that of patients with wild type KRAS (HR: 0.73; 95% CI: 0.55–0.98; P= 0.037). Conclusion: patients with mCRC and mutated KRAS who were studied in Lima have higher survival rates compared to wild type patients, being this different from what is found in the world literature.